Serotypes, antimicrobial susceptibility, and beta-lactam resistance mechanisms of clinical Haemophilus influenzae isolates from Bulgaria in a pre-vaccination period. (February 2013) - Setchanova, Lena Petrova; Kostyanev, Tomislav; Markovska, Rumyana; Miloshev, George; Mitov, Ivan Gergov
Abstract Objective: To determine the serotypes, antimicrobial susceptibility, and beta-lactam resistance mechanisms of Haemophilus influenzae strains isolated from invasive and respiratory tract infections (RTIs) prior to the introduction of Haemophilus influenzae type b (Hib) vaccination in Bulgaria. Methods: A total of 259 isolates were serotyped by polymerase chain reaction. Susceptibility to antibiotics and beta-lactamase production were determined, and DNA sequencing of the ftsI gene was performed for ampicillin non-susceptible strains. Results: The invasive H. influenzae infections in children were mainly due to serotype b (94.5% in meningitis and 88.9% in other invasive cases). Non-typeable strains (97.4%) were the most frequently found H. influenzae strains in RTIs both in children and adults. Non-susceptibility to ampicillin occurred in 22% of all strains. Ceftriaxone and levofloxacin were the most active agents tested. Ampicillin resistance occurred in 34.4% of invasive strains, and beta-lactamase production was the only mechanism found. Among respiratory tract isolates, ampicillin non-susceptible strains (18%) were classified into the following groups: beta-lactamase-positive, ampicillin-resistant (BLPAR) strains (7.2%); beta-lactamase-negative, ampicillin-non-susceptible (BLNAR) strains (8.2%); and beta- lactamase-positive, amoxicillin–clavulanate-resistant (BLPACR) strains (2.6%). Among 21 BLNAR and BLPACR strains there were 9 different patterns of multiple-amino acid substitutions in penicillin-binding protein 3. Of these, most isolates (81.0%) belonged to group II, defined by the Asn526Lys substitution. Conclusions: Beta-lactamase production was more common among invasive strains than in respiratory isolates. BLNAR and BLPACR H. influenzae were found only among respiratory tract isolates.